2014
DOI: 10.1177/0194599814549730
|View full text |Cite
|
Sign up to set email alerts
|

Low Expression of Nuclear Toll‐like Receptor 4 in Laryngeal Papillomas Transforming into Squamous Cell Carcinoma

Abstract: The expression of TLR4 may serve as a predictive marker of malignant transformation in LPs. High immunoexpression of cytoplasmic TLR4 in LSCC was associated with a more aggressive disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 24 publications
0
13
1
Order By: Relevance
“…Human patient material and in vivo models in rodents have been studied for the involvement of TLR4 in tumor progression, although the focus of these projects was mainly on the involvement of the innate immune system [ 38 ]; [ 19 ]; [ 21 ]; [ 39 , 40 ]; [ 16 ]. Studies in TLR4-deficient mice revealed that TLR4 has a supportive role in the development of chemically induced skin cancer through immune response [ 21 ]; [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Human patient material and in vivo models in rodents have been studied for the involvement of TLR4 in tumor progression, although the focus of these projects was mainly on the involvement of the innate immune system [ 38 ]; [ 19 ]; [ 21 ]; [ 39 , 40 ]; [ 16 ]. Studies in TLR4-deficient mice revealed that TLR4 has a supportive role in the development of chemically induced skin cancer through immune response [ 21 ]; [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, we think that translocation of these membrane-bound TLRs to nucleus is due to increased amount of these proteins and related signaling activity. Low nuclear expression of TLR4 has been previously linked to development of laryngeal squamous cell carcinoma [ 27 ]. However, this finding was not confirmed by other techniques.…”
Section: Discussionmentioning
confidence: 99%
“…GO functions and pathways including mitosis and cell cycle as well as Wnt, JAK/STAT and Toll-like receptor signaling pathways were markedly altered in HNSCC compared with normal controls. The mutation, abnormal expression and modification of these GOs and pathways have been frequently reported in HNSCC and other cancer types ( 34 38 ). In tumor cells, the normal energy metabolism of aerobic respiration is replaced by glycolysis, which is harnessed for accumulating intermediates of macromolecule biosynthesis, known as the 'Warburg effect' ( 39 41 ).…”
Section: Discussionmentioning
confidence: 99%